Examining the interim proposal for name change to steatotic liver disease in the US population. Issue 5 (3rd May 2023) - Ng, Cheng Han; Chan, Kai En; Muthiah, Mark; Tan, Caitlyn; Tay, Phoebe; Lim, Wen Hui; Tan, Darren Jun Hao; Fu, Clarissa Elysia; Yong, Jie Ning; Wong, Zhen Yu; Koh, Benjamin; Chew, Nicholas WS; et al.
Abstract : Background and Aims: Fatty liver is the commonest liver condition globally and traditionally associated with NAFLD. A consensus meeting was held in Chicago to explore various terminologies. Herein, we explore the proposed changes in nomenclature in a population data set from the US. Approach and Results: Statistical analysis was conducted using survey-weighted analysis. Assessment of fatty liver was conducted with vibration-controlled transient elastography. A controlled attenuation parameter of 288 dB/m was used to identify hepatic steatosis. Patients were classified into nonalcoholic steatotic liver disease, alcohol-associated steatotic liver disease, and viral hepatitis steatotic liver disease. Liver stiffness measures at ≥8.8, ≥11.7, and ≥14 kPa were used to identify clinically significant fibrosis, advanced fibrosis, and cirrhosis, respectively. A total of 5102 individuals were included in the analysis. Using a survey-weighted analysis, a total of 25.43%, 6.95%, and 0.73% of the population were classified as nonalcoholic steatotic liver disease, alcohol-associated steatotic liver disease, and viral hepatitis steatotic liver disease, respectively. A sensitivity analysis at controlled attenuation parameter of 248 dB/m and fatty liver index found similar distribution. In a comparison between nonalcoholic steatotic liver disease, alcohol-associated steatotic liver disease, and viral hepatitis steatotic liver disease, there was no significant difference between the odds of advanced fibrosis and cirrhosis between groups. However, viral hepatitis steatotic liver disease individuals were found to have a significantly higher odds of clinically significant fibrosis (OR: 3.76, 95% CI, 1.27–11.14, p =0.02) compared with nonalcoholic steatotic liver disease. Conclusions: The current analysis assessed the proposed changes based on discussions from the consensus meeting. Although the definitions are an interim analysis of discussions, steatotic liver disease respects the underlying liver etiology and reduces stigma while increasing awareness of FL among viral and alcohol-associated steatosis/steatohepatitis.